A blue light all-inorganic perovskite light-emitting diode and preparation method thereof
By using the NiOx anode interface layer and the thiolic acid compound modification layer in the perovskite light emitting diode, the crystallization performance of the perovskite thin film is controlled, and the problem of low performance of the blue light perovskite light emitting diode is solved, and the preparation and performance improvement of the blue light all-inorganic light emitting diode is achieved.
Patent Information
- Application Number
- CN202210289169.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-23
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-03-23
AI Technical Summary
The preparation method of blue light perovskite light emitting diodes in the prior art requires doping inorganic or organic matter in the perovskite light emitting layer to achieve blue light, and poor material stability, many deep energy level defect states, and difficult charge injection, resulting in low performance.
By using nickel oxide (NiOx) as the anode interface layer and thiolic acid compounds as the anode interface modification layer in the perovskite light emitting diode, the crystallization performance and band gap width of the perovskite film are regulated, and the preparation of the blue-light all-inorganic perovskite light emitting diode is realized.
This method has obvious advantages in regulating perovskite film crystallization and improving the stability of light emitting diodes. It realizes effective spectral regulation from green light to blue light, and obtains blue-light emitting electroluminescent devices based on all-inorganic perovskite material system.
Smart Images

Figure CN114759152B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of light-emitting diodes, and in particular to a blue light all-inorganic perovskite light-emitting diode and a preparation method thereof. Background Art
[0002] Metal halide perovskites show great potential in the field of optoelectronic devices due to their excellent optical and electrical properties, such as high carrier mobility, high photoluminescence quantum efficiency (PLQE), flexibly adjustable band gap and high color purity. So far, perovskite light-emitting devices with external quantum efficiency (EQE) exceeding 20% have been achieved in near-infrared and green emissions. However, the performance of blue-light-emitting perovskite devices is far from ideal, and one of the main reasons is the lack of stable and effective blue perovskite light-emitting materials. As one of the three primary light sources of red, green and blue, blue light is a prerequisite for achieving white light illumination and full-color display. Therefore, it is of great significance to develop efficient and stable blue-light perovskite light-emitting devices.
[0003] Since Richard H. Friend and Zhi-Kuang Tan et al. first reported perovskite light-emitting diodes (PeLEDs) that can work at room temperature in 2014 (Nat. Nanotechnol. 2014, 9, 687), a large number of researchers have conducted a lot of systematic research on PeLEDs through the selection of precursor materials, precursor ratio regulation, light-emitting layer defect suppression, light-emitting layer interface engineering, etc., which has steadily improved the performance of PeLEDs. After just a few years of development, the efficiency of near-infrared, red and green perovskite light-emitting diodes has exceeded 20% respectively (Nature 2018, 562, 249; Nature 2017, 550, 92). However, the efficiency of blue perovskite light-emitting diodes is still low. After spin coating the perovskite precursor solution, Max Karlsson et al. used DMF or DMSO solvent to steam treat the film to promote the exchange between chloride and bromide ions, improve the uniformity of the mixed halogen perovskite phase in the light-emitting layer, and prepare a spectrally stable blue perovskite light-emitting diode. The device brightness and EQE of the electroluminescence peak at 477nm are 2180cdm -2and 11.0% (Nature Communications 2021, 12, 361). Due to the poor stability of perovskite blue light emitting materials, many deep energy level defect states, and difficulty in charge injection, the performance of blue light perovskite diodes has always been lagging behind. At present, there are two main ways to achieve blue light emission from perovskite luminescent materials: one is to use ion mixing to achieve blue light; the other is to use the quantum confinement effect to achieve blue light. However, both approaches have their own advantages and disadvantages. Although ion mixing can easily adjust the luminescence peak position of the material, ion migration will occur under humidity, oxygen and electric field, resulting in poor material stability. The spectrum will move under external field stimulation, and its exciton binding energy is small, and the fluorescence quantum efficiency is relatively low; although quantum confinement can bind excitons and has high fluorescence quantum efficiency, the material contains too many insulating ligands, which reduces its charge transfer performance. Therefore, it is crucial to prepare a blue light-emitting perovskite light-emitting layer through a new method. Summary of the invention
[0004] In order to solve the technical problem that in the prior art, the preparation method of blue light perovskite light-emitting diodes needs to dope inorganic or organic substances in the perovskite light-emitting layer to realize blue light, the present invention provides a blue light all-inorganic perovskite light-emitting diode and a preparation method thereof. The perovskite light-emitting layer of the present invention does not need to be doped with other materials, and the preparation of the blue light all-inorganic perovskite light-emitting diode is realized by regulating the interface layer.
[0005] In order to solve the above technical problems, the technical solutions of the present invention are as follows:
[0006] The present invention provides a method for preparing a blue light all-inorganic perovskite light-emitting diode, comprising the following steps:
[0007] Step i, preparing an anode interface layer on a substrate with a patterned transparent anode layer;
[0008] Step ii, preparing an anode interface modification layer on the anode interface layer;
[0009] Step iii, growing a perovskite light-emitting layer on the anode interface modification layer;
[0010] Step iv, sequentially obtaining a cathode interface layer, a cathode interface modification layer and a cathode layer by evaporation above the perovskite light-emitting layer;
[0011] In step i, the material of the anode interface layer is nickel oxide, which is expressed as NiOx, where x is 1-1.5;
[0012] In step ii, the material of the anode interface modification layer is a mercaptic acid compound.
[0013] In the above technical solution, step i specifically includes the following steps:
[0014] Spin coating the NiOx solution evenly over the entire substrate at a spin coating speed of 2000-2500 rpm to form an anode interface layer on the surface of the patterned transparent anode layer, and then place the substrate on a hot stage for heating;
[0015] Step ii specifically includes the following steps:
[0016] The sulfhydryl compound solution is evenly coated on the entire substrate by spin coating, and the spin coating speed is controlled to be 2000-2500 revolutions per minute to form an anode interface modification layer on the surface of the anode interface layer, and then placed on a hot stage for heating.
[0017] In the above technical solution, the preparation method of the NiOx solution is as follows: NiOx powder is dispersed in deionized water to prepare a NiOx solution with a concentration of 5-20%, and ultrasonically oscillates at room temperature for 10 minutes;
[0018] The preparation method of the sulfhydryl compound solution is as follows: using ethanol as a solvent, preparing a sulfhydryl compound solution with a concentration of 5-20%, and stirring it evenly at room temperature.
[0019] In the above technical solution, the mercaptic acid compound is 11-mercaptoundecanoic acid.
[0020] In the above technical solution, in step i, the patterned transparent anode layer is an indium tin oxide electrode, and its thickness is 5-200 nanometers.
[0021] In the above technical solution, in step i, the anode interface layer is nano-NiOx, and its thickness is 5-30 nanometers.
[0022] In the above technical solution, in step iii, the perovskite light-emitting layer is pure inorganic perovskite CsPbBr3, wherein the molar ratio of CsBr to PbBr2 is 1.68:1, and the thickness is 30-60 nanometers.
[0023] In the above technical solution, in step iv, the cathode interface layer is TPBi, and its thickness is 45 nanometers; the cathode interface modification layer is LiF, and its thickness is 1 nanometer; the cathode layer is aluminum, and its thickness is 100 nanometers.
[0024] The present invention also provides a blue light all-inorganic perovskite light-emitting diode, which comprises, from bottom to top:
[0025] Substrate, patterned transparent anode layer, anode interface layer, anode interface modification layer, perovskite light emitting layer, cathode interface layer, cathode interface modification layer and cathode layer;
[0026] The material of the anode interface layer is nickel oxide (NiOx); the material of the anode interface modification layer is mercaptic acid compounds.
[0027] In the above technical solution, the material of the substrate is glass or quartz transparent material with a thickness of 1-5 mm;
[0028] The patterned transparent anode layer material is an ITO transparent conductive film with high transmittance and high conductivity, and the thickness is 5-200 nanometers;
[0029] The thickness of the anode interface layer is 5-30 nanometers;
[0030] The anode interface modification layer is 11-mercaptoundecanoic acid;
[0031] The perovskite light-emitting layer is pure inorganic perovskite CsPbBr3, wherein the molar ratio of CsBr to PbBr2 is 1.68:1, and the thickness is 30-60 nanometers;
[0032] The cathode interface layer is TPBi with a thickness of 45 nanometers;
[0033] The cathode interface modification layer is LiF with a thickness of 1 nanometer;
[0034] The cathode layer is made of metal aluminum and has a thickness of 100 nanometers.
[0035] The beneficial effects of the present invention are:
[0036] The preparation method of the blue light all-inorganic perovskite light-emitting diode of the present invention has obvious advantages in regulating the crystallization of the perovskite film and improving the stability of the perovskite light-emitting diode. The present invention aims at the problem that in the preparation method of the blue light perovskite light-emitting diode in the prior art, inorganic or organic substances need to be doped in the perovskite light-emitting layer to realize blue light. NiOx is used as the anode interface layer, and mercaptic acid compounds are used as the anode interface modification layer to effectively regulate the crystallization performance and band gap width of the perovskite film, so as to realize the effective regulation of the electroluminescence spectrum of the perovskite light-emitting device from green light to blue light, and prepare a blue light all-inorganic perovskite light-emitting diode realized by regulating the interface layer, and finally obtain a blue light emitting electroluminescent device based on the all-inorganic perovskite material system. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0038] Figure 1 The present invention is a schematic diagram of the structure of a perovskite light-emitting diode device prepared by the method of the present invention.
[0039] Figure 2It is the electroluminescence spectra of the polythiophene derivative poly (3,4-ethylenedioxythiophene) (PEDOT) doped polystyrene sulfonic acid (PSS) anode interface layer of comparative example Ⅰ (curve 1) and the perovskite film in NiOx / 11-mercaptoundecanoic acid of example 1 (curve 2).
[0040] Figure 3 These are performance spectra of the perovskite light-emitting devices of comparative example I (curve 1) and example 1 (curve 2), wherein (a) is a current density-voltage relationship diagram, (b) is a brightness-voltage relationship diagram, and (c) is a current efficiency-voltage relationship diagram.
[0041] The reference numerals in the figures indicate:
[0042] 1-substrate; 2-patterned transparent anode layer; 3-anode interface layer; 4-anode interface modification layer; 5-perovskite light-emitting layer; 6-cathode interface layer; 7-cathode interface modification layer; 8-cathode layer. DETAILED DESCRIPTION
[0043] The present invention provides a blue light all-inorganic perovskite light-emitting diode and a preparation method thereof, wherein the blue light all-inorganic perovskite light-emitting diode device structure is as follows Figure 1 As shown: from bottom to top, it includes: a substrate 1, a patterned transparent anode layer 2, an anode interface layer 3, an anode interface modification layer 4, a perovskite light-emitting layer 5, a cathode interface layer 6, a cathode interface modification layer 7 and a cathode layer 8;
[0044] The substrate 1 is made of transparent materials such as glass and quartz, and has a thickness of 1-5 mm;
[0045] The material of the patterned transparent anode layer 2 is an ITO transparent conductive film with high transmittance and high conductivity, with a thickness of 5-200 nanometers, preferably 150 nanometers;
[0046] The anode interface layer 3 is NiOx with a thickness of 5-30 nanometers;
[0047] The anode interface modification layer 4 is a mercapto acid compound, preferably 11-mercaptoundecanoic acid.
[0048] The perovskite light-emitting layer 5 is pure inorganic perovskite CsPbBr3, wherein the molar ratio of CsBr to PbBr2 is 1.68:1, and the thickness is 30-60 nanometers;
[0049] The cathode interface layer 6 is TPBi with a thickness of 45 nanometers;
[0050] The cathode interface modification layer 7 is LiF with a thickness of 1 nanometer;
[0051] The cathode layer 8 is made of metal aluminum and has a thickness of 100 nanometers.
[0052] The present invention also provides a method for preparing a blue light all-inorganic perovskite light-emitting diode, and the specific process steps and conditions are as follows:
[0053] Step 1), preparing an anode interface layer 3 on a substrate 1 with a patterned transparent anode layer 2;
[0054] Step 2), preparing an anode interface modification layer 4 on the substrate of the anode interface layer 3;
[0055] Step 3), growing a perovskite light-emitting layer 5 on the anode interface modification layer 4;
[0056] Step 4), evaporating on the perovskite light-emitting layer 5 to obtain a cathode interface layer 6, a cathode interface modification layer 7 and a cathode layer 8.
[0057] More specifically:
[0058] 1) placing a cleaned substrate 1 with a 50-200 nanometer thick patterned transparent anode layer 2 on a bracket of a spin coater, and evenly coating the entire substrate with NiOx through a 0.45 micron filter head, adjusting the spin coater rotation speed to 2000-2500 revolutions per minute, so that NiOx forms a 5-30 nanometer thick anode interface layer 3 on the surface of the transparent electrode, and heating the substrate in an oven at 120° C. for 30 minutes;
[0059] 2) Cooling the transparent anode substrate coated with NiOx, placing it on the bracket of a spin coater, evenly coating the entire substrate with the mercaptic acid solution, adjusting the spin coater rotation speed to 2000-2500 rpm, forming a monomolecular anode interface modification layer 4 on the surface of the transparent electrode, and placing it on a hot plate at 120° C. and heating it for 15 minutes;
[0060] The preparation method of the above NiOx solution is as follows: water is used as a solvent, a NiOx solution with a concentration of 5-20% is prepared, and ultrasonic oscillation is performed for 10 minutes.
[0061] The preparation method of the above-mentioned mercaptic acid solution is as follows: ethanol is used as a solvent, a mercaptic acid solution with a concentration of 5-20% is prepared, and the solution is stirred at room temperature for 1 hour.
[0062] 3) The substrate is transferred to a glove box and placed on a spin coater bracket, the mixed perovskite precursor solution is evenly dropped on the substrate 1, the spin coater is adjusted to rotate at 2000-5000 rpm, and a 30-60 nm thick perovskite light-emitting layer 5 is obtained after spin coating for 1 minute;
[0063] The preparation method of the above-mentioned perovskite precursor solution is as follows: dimethyl sulfoxide is used as a solvent, and inorganic perovskite CsPbBr3 is used as a solute, wherein the molar ratio of CsBr to PbBr2 is 1.68:1, and the solution concentration is 20-40%, and heated and stirred at 60 degrees for 3 hours, and then the heating is stopped and the stirring is continued for 12 hours;
[0064] 4) Place the product obtained in step 3) into a vacuum coating machine and evacuate the vacuum until the vacuum reaches 4×10 -4 At pascal, a cathode interface layer 6 with a thickness of 45 nanometers, a cathode interface modification layer 7 with a thickness of 1 nanometer, and a cathode layer 8 with a thickness of 100 nanometers are evaporated in sequence.
[0065] Then test.
[0066] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0067] Preparation Example of Nickel Oxide Nanoparticles
[0068] Nickel oxide (NiOx) (x means that it contains NiO, Ni2O3 and other substances, and the value range is 1-1.5); the synthesis process of NiOx is: weigh 29g of Ni(NO3)2·6H2O, then add 20mL of deionized water and stir to dissolve to obtain a dark green solution; prepare NaOH aqueous solution and adjust the pH value of Ni(NO3)2·6H2O aqueous solution to 10. After stirring for 30 minutes, the suspension was vacuum filtered and the green viscous material was washed three times with deionized water to remove soluble impurities. Then, the viscous material was transferred to a vacuum oven and heated at 80 degrees Celsius overnight to obtain a green powder. It was then transferred to a muffle furnace and calcined at 270 degrees Celsius for 2 hours to obtain dark black NiOx nanoparticles.
[0069] Comparative Example I:
[0070] The preparation method of the perovskite light-emitting diode of this comparative example comprises the following steps:
[0071] 1) Place a cleaned glass substrate with a 120-nanometer-thick patterned transparent anode ITO on the bracket of a spin coater, and evenly coat the entire substrate with PEDOT:PSS through a 0.45-micron filter head. Adjust the spin coater rotation speed to 2500 rpm to form a 30-nanometer-thick anode interface layer of PEDOT:PSS on the surface of the transparent electrode, and heat it in a 120°C oven for 30 minutes;
[0072] 2) The substrate was transferred to a glove box and placed on a spin coater bracket. The mixed perovskite precursor solution was evenly dropped on the substrate. The spin coater speed was adjusted to 2500 rpm. After 1 minute of spin coating, a 30 nm thick perovskite light-emitting layer was obtained.
[0073] The preparation method of the above-mentioned perovskite precursor solution is as follows: dimethyl sulfoxide is used as a solvent, inorganic perovskite CsPbBr3 is used as a solute, wherein the molar ratio of CsBr to PbBr2 is 1.68:1, the solution concentration is 20%, heating and stirring at 60 degrees for 3 hours, stopping heating, and continuing stirring for 12 hours;
[0074] 3) Place the product obtained in step 2) into a vacuum coating machine and evacuate the vacuum until the vacuum reaches 4×10 -4 A 45-nm-thick TPBi cathode interface layer, a 1-nm-thick LiF cathode interface modification layer, and a 100-nm-thick Al cathode layer were sequentially evaporated at 100 pascals.
[0075] Embodiment 1:
[0076] The preparation method of the blue light all-inorganic perovskite light-emitting diode of the present invention comprises the following steps:
[0077] 1) Place a cleaned glass substrate 1 with a 150-nanometer-thick patterned transparent anode ITO 2 on a bracket of a spin coater, and evenly coat the entire sheet with NiOx through a 0.45-micron filter head. Adjust the spin coater rotation speed to 2200 rpm to form a 10-nanometer-thick anode interface layer 3 of NiOx on the surface of the transparent electrode, and heat it in an oven at 120° C. for 30 minutes;
[0078] 2) Cooling the transparent anode substrate coated with NiOx, placing it on the bracket of a spin coater, and evenly coating the entire substrate with 11-mercaptoundecanoic acid solution, adjusting the spin coater rotation speed to 2200 rpm, forming a single molecule anode interface modification layer 4 on the surface of the transparent electrode, and placing it on a hot plate at 140° C. and heating it for 15 minutes;
[0079] The preparation method of the 11-mercaptoundecanoic acid solution is as follows: using ethanol as a solvent, preparing a 15% 11-mercaptoundecanoic acid solution, stirring at room temperature for 1 hour;
[0080] 3) The substrate is transferred to a glove box and placed on a spin coater bracket, the prepared perovskite precursor solution is evenly dropped on the substrate, the spin coater speed is adjusted to 2500 rpm, and a 30 nm thick perovskite light-emitting layer 5 is obtained after spin coating for 1 minute;
[0081] The preparation method of the above-mentioned perovskite precursor solution is as follows: dimethyl sulfoxide is used as a solvent, inorganic perovskite CsPbBr3 is used as a solute, wherein the molar ratio of CsBr to PbBr2 is 1.68:1, the solution concentration is 20%, heating and stirring at 60 degrees for 3 hours, stopping heating, and continuing stirring for 12 hours;
[0082] 4) Place the product obtained in step 3) into a vacuum coating machine and evacuate the vacuum until the vacuum reaches 4×10 -4 A 45 nm thick TPBi cathode interface layer 6, a 1 nm thick LiF cathode interface modification layer 7, and a 100 nm thick Al cathode layer 8 were sequentially evaporated at 100 pascals.
[0083] Embodiment 2:
[0084] The preparation method of the blue light all-inorganic perovskite light-emitting diode of the present invention comprises the following steps:
[0085] 1) Place a cleaned glass substrate 1 with a 150-nanometer-thick patterned transparent anode ITO 2 on a bracket of a spin coater, and evenly coat the entire sheet with NiOx through a 0.45-micron filter head. Adjust the spin coater rotation speed to 2500 rpm to form a 5-nanometer-thick anode interface layer 3 of NiOx on the surface of the transparent electrode, and heat it in an oven at 120° C. for 30 minutes;
[0086] 2) Cooling the transparent anode substrate coated with NiOx, placing it on the bracket of a spin coater, and evenly coating the entire substrate with 11-mercaptoundecanoic acid solution, adjusting the spin coater rotation speed to 2200 rpm, forming a single molecule anode interface modification layer 4 on the surface of the transparent electrode, and placing it on a hot plate at 140° C. and heating it for 15 minutes;
[0087] The preparation method of the 11-mercaptoundecanoic acid solution is as follows: using ethanol as a solvent, preparing a 11-mercaptoundecanoic acid solution with a concentration of 5%, and stirring at room temperature for 1 hour;
[0088] 3) The substrate is transferred to a glove box and placed on a spin coater bracket, the prepared perovskite precursor solution is evenly dropped on the substrate, the spin coater speed is adjusted to 2500 rpm, and a 60 nm thick perovskite light-emitting layer 5 is obtained after spin coating for 1 minute;
[0089] The preparation method of the above-mentioned perovskite precursor solution is as follows: dimethyl sulfoxide is used as a solvent, inorganic perovskite CsPbBr3 is used as a solute, wherein the molar ratio of CsBr to PbBr2 is 1.68:1, the solution concentration is 40%, heating and stirring at 60 degrees for 3 hours, stopping heating, and continuing stirring for 12 hours;
[0090] 4) Place the product obtained in step 3) into a vacuum coating machine and evacuate the vacuum until the vacuum reaches 4×10 -4 A 45 nm thick TPBi cathode interface layer 6, a 1 nm thick LiF cathode interface modification layer 7, and a 100 nm thick Al cathode layer 8 were sequentially evaporated at 100 pascals.
[0091] Embodiment 3:
[0092] The preparation method of the blue light all-inorganic perovskite light-emitting diode of the present invention comprises the following steps:
[0093] 1) Place a cleaned glass substrate 1 with a 150-nanometer-thick patterned transparent anode ITO 2 on a bracket of a spin coater, and evenly coat the entire sheet with NiOx through a 0.45-micron filter head. Adjust the spin coater rotation speed to 2000 revolutions per minute to form a 30-nanometer-thick anode interface layer 3 of NiOx on the surface of the transparent electrode, and heat it in an oven at 120° C. for 30 minutes;
[0094] 2) Cooling the transparent anode substrate coated with NiOx, placing it on the bracket of a spin coater, and evenly coating the entire substrate with 11-mercaptoundecanoic acid solution, adjusting the spin coater rotation speed to 2200 rpm, forming a single molecule anode interface modification layer 4 on the surface of the transparent electrode, and placing it on a hot plate at 140° C. and heating it for 15 minutes;
[0095] The preparation method of the 11-mercaptoundecanoic acid solution is as follows: using ethanol as a solvent, preparing a 11-mercaptoundecanoic acid solution with a concentration of 20%, and stirring at room temperature for 1 hour;
[0096] 3) The substrate is transferred to a glove box and placed on a spin coater bracket, the prepared perovskite precursor solution is evenly dropped on the substrate, the spin coater speed is adjusted to 2000 rpm, and a 40 nm thick perovskite light-emitting layer 5 is obtained after spin coating for 1 minute;
[0097] The preparation method of the above-mentioned perovskite precursor solution is as follows: dimethyl sulfoxide is used as a solvent, inorganic perovskite CsPbBr3 is used as a solute, wherein the molar ratio of CsBr to PbBr2 is 1.68:1, the solution concentration is 30%, heating and stirring at 60 degrees for 3 hours, stopping heating, and continuing stirring for 12 hours;
[0098] 4) Place the product obtained in step 3) into a vacuum coating machine and evacuate the vacuum until the vacuum reaches 4×10 -4 A 45 nm thick TPBi cathode interface layer 6, a 1 nm thick LiF cathode interface modification layer 7, and a 100 nm thick Al cathode layer 8 were sequentially evaporated at 100 pascals.
[0099] Through the above multiple embodiments and comparative examples, it can be understood that:
[0100] Figure 2 It is the electroluminescence spectrum of comparative example Ⅰ (curve 1) and example 1 (curve 2). It can be seen from the figure that the electroluminescence peak of example 1 is located at 495 nanometers, showing blue light emission, while the luminescence peak of comparative example 1 is located at 515 nanometers, showing green light emission. The blue shift of the spectrum is mainly due to the influence of the NiOx / 11-mercaptoundecanoic acid at the anode interface on the crystallization performance and bandgap width of the all-inorganic perovskite system. Figure 3 The performance spectra of the perovskite light-emitting devices of Comparative Example Ⅰ (curve 1) and Example 1 (curve 2) are shown in Table 1. The specific performance parameters are given in Table 1. It can be seen that compared with Comparative Example Ⅰ, the electroluminescent wavelength is shorter, and its luminescence peak is located in the blue light band. However, due to the large number of defects in the blue light perovskite film and the deep valence band of the blue light emitting perovskite film, there is a lack of efficient hole transport materials with energy level matching, so that its performance lags behind that of the green light Comparative Example Ⅰ device.
[0101] Table 1. Performance parameters of perovskite light-emitting devices
[0102]
[0103]
[0104] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a blue light all-inorganic perovskite light-emitting diode, comprising the following steps: Step i, preparing an anode interface layer on a substrate with a patterned transparent anode layer; Step ii, preparing an anode interface modification layer on the anode interface layer; Step iii, growing a perovskite light-emitting layer on the anode interface modification layer; Step iv, sequentially obtaining a cathode interface layer, a cathode interface modification layer and a cathode layer by evaporation above the perovskite light-emitting layer; It is characterized in that In step i, the material of the anode interface layer is nickel oxide, which is expressed as NiOx, where x is 1-1.5; In step ii, the material of the anode interface modification layer is a mercaptic acid compound.
2. The preparation method according to claim 1, characterized in that: Step i specifically includes the following steps: Spin coating the NiOx solution evenly over the entire substrate at a spin coating speed of 2000-2500 rpm to form an anode interface layer on the surface of the patterned transparent anode layer, and then place the substrate on a hot stage for heating; Step ii specifically includes the following steps: The sulfhydryl compound solution is evenly coated on the entire substrate by spin coating, and the spin coating speed is controlled to be 2000-2500 revolutions per minute to form an anode interface modification layer on the surface of the anode interface layer, and then placed on a hot stage for heating.
3. The preparation method according to claim 2, characterized in that: The preparation method of the NiOx solution is as follows: NiOx powder was dispersed in deionized water to prepare a NiOx solution with a concentration of 5-20%, and ultrasonically vibrated at room temperature for 10 minutes; The preparation method of the sulfhydryl compound solution is as follows: Using ethanol as solvent, prepare a 5-20% sulfhydryl compound solution, and stir it evenly at room temperature.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The mercaptic acid compound is 11-mercaptoundecanoic acid.
5. The preparation method according to claim 1, characterized in that: In step i, the patterned transparent anode layer is an indium tin oxide electrode with a thickness of 5-200 nanometers.
6. The preparation method according to claim 1, characterized in that: In step i, the anode interface layer is nano-NiOx, and its thickness is 5-30 nanometers.
7. The preparation method according to claim 1, characterized in that: In step iii, the perovskite light-emitting layer is pure inorganic perovskite CsPbBr3, wherein the molar ratio of CsBr to PbBr2 is 1.68:1, and the thickness is 30-60 nanometers.
8. The preparation method according to claim 1, characterized in that: In step iv, the cathode interface layer is TPBi, and its thickness is 45 nanometers; the cathode interface modification layer is LiF, and its thickness is 1 nanometer; the cathode layer is aluminum, and its thickness is 100 nanometers.
9. A blue light all-inorganic perovskite light-emitting diode prepared by the preparation method of claim 1, comprising, from bottom to top: Substrate, patterned transparent anode layer, anode interface layer, anode interface modification layer, perovskite light emitting layer, cathode interface layer, cathode interface modification layer and cathode layer; It is characterized in that The material of the anode interface layer is nickel oxide; the material of the anode interface modification layer is mercaptic acid compounds.
10. The blue light all-inorganic perovskite light-emitting diode according to claim 9, characterized in that: The substrate is made of glass or transparent quartz material with a thickness of 1-5 mm; The patterned transparent anode layer material is an ITO transparent conductive film with high transmittance and high conductivity, and the thickness is 5-200 nanometers; The thickness of the anode interface layer is 5-30 nanometers; The anode interface modification layer is 11-mercaptoundecanoic acid; The perovskite light-emitting layer is pure inorganic perovskite CsPbBr3, wherein the molar ratio of CsBr to PbBr2 is 1.68:1, and the thickness is 30-60 nanometers; The cathode interface layer is TPBi with a thickness of 45 nanometers; The cathode interface modification layer is LiF with a thickness of 1 nanometer; The cathode layer is made of metal aluminum and has a thickness of 100 nanometers.
Citation Information
Patent Citations
Perovskite blue light emitting diode with high efficiency and stable light emitting color
CN110649171A
CsPbX<3> perovskite nanocrystalline electroluminescent diode with self-assembled multi-dimensional quantum well
CN110943178A